Entomopathogenic nematodes as potential biological control agents of Popillia japonica (Coleoptera, Scarabaeidae) in Piedmont Region (Italy). (31st October 2017) - Marianelli, L.; Paoli, F.; Torrini, G.; Mazza, G.; Benvenuti, C.; Binazzi, F.; Sabbatini Peverieri, G.; Bosio, G.; Venanzio, D.; Giacometto, E.; Priori, S.; Koppenhöfer, A. M.; et al.
Abstract: In 2014, the Japanese beetle Popillia japonica (Coleoptera: Scarabaeidae) was first spotted in northern Italy in the Nature Park of the Ticino Valley, its first detection in continental Europe. This polyphagous invasive species has the potential to cause serious losses to horticulture and agriculture. Particularly for its management in a Nature Park, environmentally friendly strategies are necessary. To develop baseline data for a biological control approach to the Italian outbreak of P. japonica, we conducted laboratory and field experiments testing several indigenous and commercial strains of the entomopathogenic nematode (EPN) species Heterorhabditis bacteriophora and Steinernema carpocapsae against P. japonica larvae. In the laboratory, strains of H. bacteriophora caused greater mortality (ranging from 57% to 100%) than those of S. carpocapsae (3% to 77%). In micro‐plot field tests carried out at three different times, the most virulent indigenous EPN strain, H. bacteriophora ItH‐LU1, showed again the best results ranging from 44% to 93% against young larvae. Finally, in a large‐plot field trial, the commercial H. bacteriophora product provided 46% larval mortality. This study shows that H. bacteriophora strains have good potential as biological control agents of larvae of the invasive P. japonica in northern Italy.